The role of vitamin D and other vitamins in the development and treatment of immune-mediated skin diseases - F. I. Rusnak (Лечащий Врач, 2024)
Background. Psoriasis is classified as a systemic immune-mediated inflammatory skin disease, with a frequency of 2-3%. Taking vitamins for psoriasis accelerates the healing processes, normalizes metabolism, relieves the symptoms of the disease, improves the condition of the skin, hair and nails.Objective. The role of vitamin D in the pathogenesis of various skin diseases has been shown, and vitamin D deficiency was more often observed in patients with atopic dermatitis and psoriasis, which suggests an important role of vitamin D in the pathogenesis of these common skin diseases. Low levels of 25-hydroxyvitamin D (the transport form of vitamin D, which characterizes vitamin D availability) are found in numerous dermatological diseases, including psoriasis. The interaction between intestinal bacteria and the immune system occurs at several levels and vitamin D is an important mediator in this dynamic.Conclusion. To prevent and successfully treat immuno-mediated inflammatory skin diseases, including psoriasis, it is necessary to ensure the physiological needs of the body in vitamins A, E, D, C, B1, B6, B9, B12, PP. Vitamin and mineral complexes used in the form of drinks not only normalize the vitamin status of the body, but also contribute to the normalization of the microbiota intestinal tract, which affects the health of the skin. In severe skin lesions – psoriasis, the topical vitamin D preparation calcipotriol is successfully used.